Positif Correlation of Online Game Addiction and Depression Level of Adolescent - Wiwik Widiyawati; Helmi Ardiansyah Arby (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2022)
Nowadays, online game become a lifestyle toward young generations and tends to become addiction. Addiction to online games has a risk of suffering from Asperg's syndrome, autism, and is prone to various disorders and mental disorders. The purpose of this study was to analyze the correlation of online game addiction and depression levels of adolescents at SMAN 2 Bangkalan. This study used correlation analytic method with cross sectional design. The population was 410 students of class XII from science and social program at Public Senior high School (SMAN) 2 Bangkalan. The sample was 202 respondents taken by random sampling technique. The data collection used questionnaire then analyzed by using the Spearman Rho rank test (p < 0.05). The results showed most of the respondents or 138 students (68.3%) were in the category of moderate addiction, 31 students (15.3%) in the category of mild addiction, a small proportion or 28 students. (13.9%) were in the category ofsevere addiction, and 5 students (2.5%) not addicted to games. It could be seen that the distribution of respondents based on the level of depression showed 157 students (77.7%) had mild depression, 34 adolescents (16.8%) had a moderate depression, 5 students (2.5%) had severe depression, and 6 students (3.0%) had no depression. Based on the results of the analysis using the Spearman rank test, it was found that p value = 0.017 (<0.05), meant that there was a significant correlation between online game addiction and depression levels of adolescents. It is necessary to increase the knowledge of students about addiction and the level of depression due to online games. The society have to teach their children the dangerous side effect of addiction toward online games.